The quality of advocacy services in primary school social work from the perspective of Vietnamese teachers - Ha Van Hoang; Pham Thi Kieu Duyen (International Journal of Evaluation and Research in Education (IJERE), 2026)
This study aimed to assess the level of satisfaction among primary school teachers with advocacy services in school social work and to identify influencing factors. A quantitative method was applied through a questionnaire survey of 398 primary school teachers, focusing on evaluating aspects of advocacy services such as reliability, responsiveness, professional competence, empathy, and implementation conditions. The results showed that the overall satisfaction level of teachers was quite high (M=4.01, SD=0.27), and all components of the service were viewed positively. Simultaneously, factors such as gender, age, location, and region influenced how teachers evaluated the quality of the service, while years of service and educational level had only a limited impact. On the other hand, all service components showed a positive correlation with the level of satisfaction with advocacy services in school social work. In this study, responsiveness, reliability, empathy, and implementation conditions showed statistically significant results. Therefore, the study suggests policy directions and further research, particularly in applying the service quality (SERVQUAL) model to measure and improve aspects of social work services.